Genetic and functional analysis of the PDB6 locus in Paget's disease of bone - Silva, Iris Alexandra Lopes da (2017)
Tese de doutoramento, Ciências Biomédicas, Departamento de Ciências Biomédicas e Medicina, Universidade do Algarve, 2015